Stranger things holiday specials ebook - Champagne, Keith (Dark Horse Comics, LLC., 2022)
Get the first three Stranger Things Holiday Specials all in one package—with stories that are both heartwarming and terrifying! Three separate stories good for any season: Eleven gets introduced to everyone's favorite Christmas stories, Will tells the other boys the scariest Hawkins Halloween story EVER, and officers Powell and Callahan investigate strange events they will be lucky to survive… to survive. Collects the Halloween Special, Winter Special, and Summer Special!